Alcohol use disorder as a possible predictor of electroconvulsive therapy response - Aksay, Suna Su; Janke, Christoph; Sartorius, Alexander (The journal of ECT, 2017)
Two rapidly acting antidepressive treatment forms, namely, electroconvulsive therapy (ECT) and ketamine, possibly share a common mechanism of action primarily involving alterations of neurotransmission (glutamate and γ-aminobutyric acid levels). Because patients receiving ketamine and with a coexistent family history of an alcohol use disorder (AUD) seem to benefit from consistent and longer lasting antidepressive effects, we hypothesized better treatment response in ECT patients with an own history or a family history of an AUD. One hundred forty-one psychiatric inpatients with a major depressive episode, who were treated with ECT, were enrolled into this retrospective study. Age, sex, family or personal history of alcohol or benzodiazepine use disorder, ECT response data, and ECT treatment-related data were collected and analyzed with ordinal logistic regression and Fisher exact tests. Twenty-one percent of all patients had their own history of an AUD, 11% had their own history of a benzodiazepine use disorder, and 11% reported on a positive family history of alcohol or benzodiazepine use disorder. The logistic regression analyses revealed that only patient's own history of an AUD predicts a better ECT response (P = 0.031; odds ratio, 2.1; Fisher exact test, P = 0.006). Within the limitations of a retrospective study, a history of an AUD seems to be a positive predictor for an ECT response in patients experiencing a major depressive episode, which has not been found in 2 earlier studies. Findings are in line with neurobiological hypotheses of excitatory/inhibitory neurotransmitter changes with ketamine and ECT.